The Impact of Internships on Nursing Students During the Epidemic and the Response of Clinical Preceptors (International Journal of Studies in Nursing, 2024)
Background: For nursing students’ inadequate experience in clinical internships due to the COVID-19 epidemic, most schools responded with adjustment involving various modes of teaching. Nevertheless, the impact on nursing students has been an important issue. Aim: From the perspective of clinical preceptors, to investigate the learning impact on nursing students during the epidemic and the response of clinical preceptors. Subject and methods: A total of 9 clinical preceptors were interviewed following focus group methodology based on an outline for self-developed structured interview. The results of interviews were further analyzed using qualitative research. Results: The follows were found from the perspective of clinical preceptors: The impacts on students during the epidemic include “lack of real-life communication”, “lack of clinical scenario”, “less mature skills”, and “worry”. The responses from clinical preceptors during the epidemic include: “comfort or care”, “providing protective equipment”, and “teaching students in accordance with their aptitude”. The epidemic affects the capability of nursing students in clinical care, for which clinical preceptors expect the hospital end to “provide adequate manpower”, “prolong the adaptation period for students” to assist nursing students in adapting to the workplace. Conclusion: Nursing students’ internships at hospitals were affected during the epidemic, which further leads to the inadequate capability in clinical care from nursing students. Therefore, providing individual guidance by workplaces is an essential measure.